Influence of Marital Infection with Receiving Hepatitis B Vaccine and Hepatitis B Infection in Women Attending Antenatal at Uttaradit Hospital - Supabroop, Marilyn; Kusirirat, Chuchart; Boonkruechoo, Porntip; Mated, Pradab (Health Science Clinical Research, 2020)
Object: The study of prevalence of chronic hepatitis B virus infection Pregnancy women and immune persons among them was done for counseling service to the Antenatal care ones with chronic hepatitis Band HB immunization for the non-immune ones. Study Design: retrospective research design cohort Research: Location Antenatal care,Gestation Unit in Uttaradit Hospital Methods: This cross-sectional analytic study analyzed the relationship between December 1, 2018 to June 30, 2018 were included. positive HBeAg Pregnancy women 5 case and negative HBeAg Pregnancy 113 case, using exact probability test and t-test to calculate estimated odds ratio and95% Confidence Antenatal care Results: Hepatitis B infection in married couples increased risk of hepatitis B infection 2.58 times. But when considered by the history of vaccination, the pregnant women who have been vaccinated Hepatitis B infection in married couples increased risk of hepatitis B infection 0 times. While thepregnant women who have not been vaccinated Hepatitis B infection in married couples increased risk of hepatitis B infection 12.5 times. Conclusions: infected with hepatitis B virus correlates with pregnant women infected Upper risk 2.58 OR = 0,95% (P=0.401) In pregnant women no vaccine infected with hepatitis Bvirusmen Upperrisk 12.5 significantly OR = 12.5, 95% CI=0.13,999.46 , p = 0.03) In pregnant women vaccine infected with hepatitis Bvirusmen Upperrisk 0 Keywords: Hepatitis B disease, Pregnant Women, Hepatitis B Vaccine